2014
DOI: 10.1080/10826068.2014.907184
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Partial Characterization of an Acidic α-Amylase from a Newly IsolatedBacillus subtilisZJ-1 that may be Applied to Feed Enzyme

Abstract: An amylase-producing strain was isolated from soy sauce and designated as Bacillus subtilis ZJ-1. Purification of α-amylase from B. subtilis ZJ-1 to homogeneity by ethanol fractionation, ultrafiltration, and Sephadex G-100 gel filtration resulted in recovery of 8.9% and a specific activity of 542.7 U/mg protein. The molecular mass was estimated to be 58 kD by sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE). The enzyme reached its maximum activity at a pH of 5.0 and a temperature of 50°C. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Lin et al 33 suggested that enzyme was activated with Ca 2+ , while it was inhibited in the presence of Hg 2+ . The effect of various metal ions on purified α-amylase activity was reported by Mamo and Gessesse 34 , Aguloglu Fincan and Enez 20 , and Liu et al 35 . Our results are very close to their studies.…”
Section: Effect Of Different Cations and Inhibitors On Purified α-Amymentioning
confidence: 66%
“…Lin et al 33 suggested that enzyme was activated with Ca 2+ , while it was inhibited in the presence of Hg 2+ . The effect of various metal ions on purified α-amylase activity was reported by Mamo and Gessesse 34 , Aguloglu Fincan and Enez 20 , and Liu et al 35 . Our results are very close to their studies.…”
Section: Effect Of Different Cations and Inhibitors On Purified α-Amymentioning
confidence: 66%
“…One of the most widely used feed additives in the poultry industry is α-amylase, which can improve starch digestibility and poultry performance . It has been reported that acidic α-amylase from Bacillus subtilis is a good candidate for use as a chicken feed enzyme because of its high thermostability during the pelleting process of feed production . In another study, α-amylase from A.…”
Section: Resultsmentioning
confidence: 99%
“…63 It has been reported that acidic α-amylase from Bacillus subtilis is a good candidate for use as a chicken feed enzyme because of its high thermostability during the pelleting process of feed production. 64 In another study, α-amylase from A. oryzae was used as a supplement for ruminant diets to improve animal productivity by modifying starch. 65 Additionally, α-amylase was added in combination with other enzymes in the poultry diet to increase the digestibility of feed.…”
Section: ■ Results and Discussionmentioning
confidence: 99%